Faktor Yang Mempengaruhi Konservatisme Akuntansi dengan Altman Z-Score Sebagai Variabel Moderasi - Baiq Jenny Audia Grenaldin; Defel Septian; Khairunnisa (Jurnal Riset Manajemen dan Akuntansi, 2026)
The application of accounting conservatism is important to maintain the reliability of financial statements, especially in uncertain economic conditions and potential conflicts between management and shareholders. This is reflected in the case of PT Indofarma Tbk (INAF), which experienced financial reporting irregularities that led to fraud and reduced public trust. This study aims to examine and analyze the influence of growth opportunity, return on equity, and capital intensity on accounting conservatism with Altman Z-Score as a moderating variable in non-cyclical consumer companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study is quantitative research with an associative approach. The research sample consisted of 68 companies selected using purposive sampling. The data analysis methods used were Multiple Linear Regression and Moderated Regression Analysis (MRA) with the help of IBM SPSS 31 software. The results showed that growth opportunity had a significant effect on accounting conservatism with a regression coefficient value of -0.044. Return on equity has a significant effect on accounting conservatism with a regression coefficient value of -0.020. Meanwhile, capital intensity has a significant positive effect on accounting conservatism. Altman Z-Score is unable to moderate the relationship between growth opportunity, return on equity, and capital intensity on accounting conservatism. These findings indicate that the financial health of companies neither strengthens nor weakens the influence of independent variables on the application of accounting conservatism principles in non-cyclical consumer companies listed on the Indonesia Stock Exchange for the period 2020-2024.